2018
DOI: 10.1017/jrr.2018.15
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Japanese Version of the Multidimensional Stress Questionnaire for Couples: Factor Structure, Validity and Reliability

Abstract: We validated the Japanese version of the Multidimensional Stress Questionnaire for Couples (MSQ) and examined construct validity and reliability. We conducted an online longitudinal survey of 300 husbands and 300 wives. The Japanese version of the MSQ (MSQ-J) had a two-factor structure centred on internal and external stressors. The internal-stressor factor showed sufficient validity and reliability, indicating its suitability for measuring marital stressors. The external-stressors factor also showed acceptabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 25 publications
0
3
1
5
Order By: Relevance
“…The results of this survey also showed that the psychological capital scores of two-child nurses differed according to age, years of service, job title, and monthly income (P<0.05), which is consistent with the results reported in the literature (15). This survey showed that the dyadic stress score of nurses with two children was 34.48±6.18, which is at a moderate level but higher than the results of the study by Kurosawa et al (9). The possible reasons are as follows: on the one hand, nurses who have had a second child face external pressures such as work pressure, financial pressure, and child-related pressure; on the other hand, they may also experience internal pressure from their spouses, such as taking on family affairs, daily conflicts, and relationship tensions caused by childcare or pressure due to the health of their partner.…”
Section: Psychological Capital Dyadic Stress and Job Burnout In Nurses With Two Childrencontrasting
confidence: 69%
See 1 more Smart Citation
“…The results of this survey also showed that the psychological capital scores of two-child nurses differed according to age, years of service, job title, and monthly income (P<0.05), which is consistent with the results reported in the literature (15). This survey showed that the dyadic stress score of nurses with two children was 34.48±6.18, which is at a moderate level but higher than the results of the study by Kurosawa et al (9). The possible reasons are as follows: on the one hand, nurses who have had a second child face external pressures such as work pressure, financial pressure, and child-related pressure; on the other hand, they may also experience internal pressure from their spouses, such as taking on family affairs, daily conflicts, and relationship tensions caused by childcare or pressure due to the health of their partner.…”
Section: Psychological Capital Dyadic Stress and Job Burnout In Nurses With Two Childrencontrasting
confidence: 69%
“…The translated and revised Multidimensional Stress Questionnaire for Couples (9) was used to evaluate the dyadic stress status of nurses with two children. The scale is divided into two dimensions of internal pressure (10 items) and external pressure (8 items), with a total of 18 items.…”
Section: Dyadic Stress Scalementioning
confidence: 99%
“…A spillover (tovagyűrűző) hatás (Story & Repetti, 2006) által ugyanis az extradiádikus stressz továbbgyűrűzik a párkapcsolati térben intradiádikus (a párkapcsolatból származó) stresszként, a megnövekedett intradiádikus stressz pedig moderálja az extradiádikus stressz kapcsolatát a párkapcsolati elégedettséggel (Falconier, Nussbeck, Bodenmann, Schneider, & Bradbury, 2015). Mind az extradiádikus, mind az intradiádikus stressz magasabb mértéke alacsonyabb párkapcsolati elégedettséggel jár együtt (Kurosawa & Yokotani, 2018). Ugyanakkor fontos különbséget tennünk a rövid, valamint a hosszú ideig fennálló stressz között.…”
Section: Diádikus Stressz éS Diádikus Megküzdésunclassified
“…Bodenmann (2007) a mérőeszköz pszichometriai mutatóit nem publikálta, ezért más vizsgálatokban kapott eredményekre tudunk hivatkozni a megbízhatóságot és az érvényességet illetően. A korábbi kutatásokban az MSQ-C skáláinak belső konzisztenciáját az angol változat esetében 0,84-0,86 (Falconier és mtsai, 2015) és 0,66-0,82 (Merz és mtsai, 2014), a japán nyelvű esetében 0,84-0,95 (Kurosawa & Yokotani, 2018), a kínai nyelvűnél 0,69-0,80 (Xu, Hilpert, Nussbeck, & Bodenmann, 2016) közötti Cronbach-αértékek jellemezték. Az intra-és extradiádikus stresszt mérő faktorok pedig mindegyik esetben jól elkülöníthetőnek bizonyultak.…”
Section: Diádikus Stressz éS Diádikus Megküzdésunclassified
See 1 more Smart Citation